The Food Security Decision Support System is integrated into a national food security strategy - CGIAR Research Program on Climate Change, Agriculture and Food Security (2020)
The Food Security Decision Support System (FSDSS) co-developed by CCAFS scientists has been integrated into the National Food Security Information System (SIINSAN).